APPLICATION OF COCONUT FIBER IN CEMENTITIOUS MATRIX - Silva, Everton; Marques, Maria; Fornari Junior, Celso (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
In view of the wide variety of natural fibers with potential for reinforcing composite materials usedin the production of mortars and concretes for civil construction, it becomes essential to theknowledge of the potential of these materials through its characterization to best apply them.Natural fibers exist in abundance and have the use caused by being biodegradable, renewable, forits availability at low cost, often as waste, enabling the production of composites alsoeconomically viable. This paper presents a brief review about current searches that are beingdeveloped in terms of reuse of coconut fiber in construction, more specifically in concretes andmortars.